2020
DOI: 10.1111/imm.13246
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK signaling mediates retinoic acid‐induced CD103 expression in human dendritic cells

Abstract: Retinoic acid (RA) is an active derivative of vitamin A and a key regulator of immune cell function. In dendritic cells (DCs), RA drives the expression of CD103 (integrin a E), a functionally relevant DC subset marker. In this study, we analyzed the cell type specificity and the molecular mechanisms involved in RA-induced CD103 expression. We show that RA treatment caused a significant up-regulation of CD103 in differentiated monocyte-derived DCs and blood DCs, but not in differentiated monocyte-derived macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Pellet by gentle centrifugation at 100 g for 2 min. 2) Preparation of MoDCs: a Prepare culture of MoDCs from blood monocytes using standard protocols ( Sebrell et al, 2019 ; Roe et al, 2020 ). b Harvest MoDCs by vigorous pipetting and washing with PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pellet by gentle centrifugation at 100 g for 2 min. 2) Preparation of MoDCs: a Prepare culture of MoDCs from blood monocytes using standard protocols ( Sebrell et al, 2019 ; Roe et al, 2020 ). b Harvest MoDCs by vigorous pipetting and washing with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…a Prepare culture of MoDCs from blood monocytes using standard protocols ( Sebrell et al, 2019 ; Roe et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Of course, other cellular signaling pathways besides GM-CSF are involved in regulating CD103 expression on cDCs. For example, TGFb and retinoic acid also reportedly induced CD103 expression (Iliev et al, 2009;Roe et al, 2017;Roe et al, 2020). Whether LPS and P. aeruginosa alter CD103 expression in response to these stimuli remains unknown, but definitely of interest.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that activation of the p38 MAPK signaling pathway contributes to enhance PGC-1α level and promote mitochondrial biogenesis [ 29 ]. It has been shown that RA increases p38 MAPK phosphorylation level and improves its function [ 30 , 31 ]. Although several studies have revealed that VA and its metabolite (retinoic acid) affect myofiber type composition, whether VA affects the development of myofiber type in sheep is still unknown.…”
Section: Introductionmentioning
confidence: 99%